Analisis Protein dan Daya Terima Cookies Biji Nangka dengan Penambahan Tepung Ikan Gabus - Viliantina, Rifka Wuri; Rohmawati, Ninna; Antika, Ruli Bahyu (NUTRITURE JOURNAL, 2023)
Background: Malnutrition is one of the nutritional problems in Indonesia caused by the lack of consumption of food or protein energy over a certain period, so it can be said that the nutritional status of toddlers depends on the food conditions at the time. Fulfillment the nutritional substance of toddler can be overcome by providing additional food in the form cookies. Researchers want to modify jackfruit seed cookies with the addition of snakehead fish flour to obtain food products with high protein content. Objective: The study aimed to analyze the protein content and acceptability of jackfruit seeds cookies with the addition of snakehead fish flour. Method: This research was a Quasi-Experimental using a Posttest-Only Control Group Design. The research sample consisted of 25 students at SDN Lenteng Timur 1. Results: Protein content with 4 levels of treatment (X0, X1, X2, X3) is 7.54; 8.38; 9,12; and 9.79. The higher the addition of snakehead fish flour, the higher the protein content of jackfruit seed cookies. Jackfruit seed cookies with the addition of 5% snakehead fish flour were cookies that were liked by the panelists. Conclusion:The addition of snakehead fish flour had a significant difference in protein content. The jackfruit seed cookies were accepted by the panelists in terms of color, aroma, taste and texture, but based on statistical results only the acceptability of aroma and taste had significant differences. The recommended jackfruit seed cookies are X1 with the addition of 5% snakehead fish flour.. Keywords: Jackfruit seeds; Cookies; Malnutrition; Fish cork; Proteins